Malaysian Refining Company Sdn Bhd (MRCSB) / Muhammad Danish Haqeem Azlan - Azlan, Muhammad Danish Haqeem (Faculty Of Chemical Engineering, 2022)
This industrial training report of Muhammad Danish Haqeem bin Azlan requires him to participate in an industrial training programme that lasts for a total of six months and is divided into 24 weeks before he can finish his Diploma courses. Beginning an industrial training programme at Malaysian Refining Company Sdn Bhd on the 21st of February 2022 and continuing it until the 4th of August 2022 under the direction of Mr. Farahan. The goal of this programme is to ensure that participants successfully complete the required coursework to not only earn their diploma but also get their degree from the institution. Before graduating, individuals should get training in the form of job experience that is relevant to their professional growth. The term "industrial training" will be defined and a description of the goals of industrial training will be provided in the first chapter of this study. In this section, the specific goals of the industrial training report and the industrial report are broken down in further depth. A comprehensive review of the organisation and its divisions can be found in the report's second chapter. The next chapter provides an overview of the many responsibilities and assignments that are part of the weekly industrial training activities that are carried out. The next chapter is my summary and details of tasks for the past 24 weeks. Problems encountered and recommendations were given from my own feedback to further enhance the Industrial Training syllabus to a higher and competitive standard. As a result of being an engineer at Petronas, I was able to bring my goals and ambitions into appropriate focus. Being an engineer is not an easy job but receiving advice and assistance from my supervisor and other members of the Distillation Team was a positive experience for me. As a result, I am more motivated than ever to take my work as an engineer seriously. I really hope that my contributions to the organisation and to my cherished home nation of Malaysia can be noticed by others.